A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation

The Ag9(SiO4)2NO3/Co(OH)2 composite catalyst was prepared by co-precipitation method, which solved the problems of the existing Ag9(SiO4)2NO3 preparation process and low CO2 photothermal reduction performance, and achieved efficient CO2 photothermal reduction performance.

CN119488933BActive Publication Date: 2025-04-04GANSU WANZHANXING TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510082775.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-04
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing Ag9(SiO4)2NO3 preparation process is complex, and the CO2 photothermal reduction performance is low, making it difficult to meet the needs of efficient conversion of CO2.

Method used

Ag9(SiO4)2NO3/Co(OH)2 composite catalyst was prepared by co-precipitation method. The specific surface area of ​​the product was increased by adding a modifier, and the co-precipitation reaction was carried out under room temperature using a sol system.

Benefits of technology

The preparation process is simplified, the specific surface area and reaction activity of the catalyst are improved, the adsorption and diffusion capacity of CO2 are enhanced, and the performance of photothermal reduction of CO2 is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488933B_ABST
    Figure CN119488933B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, in particular to a method for preparing a composite photothermal reduction CO2 catalyst by a coprecipitation method, comprising the following preparation steps: S1. adding 2-6g of nano-SiO2 powder and 2-8g of NaOH to 48-60g of a modifier to obtain a silicon source solution; S2. slowly adding 25-33g of silver nitrate powder to the silicon source solution under a condition of mechanical stirring to obtain a preliminary mixed solution; S3. slowly adding 0.4-1.3g of cobalt nitrate powder to the preliminary mixed solution under a condition of mechanical stirring until precipitation is complete, and filtering to obtain a coprecipitation product; S4. washing the coprecipitation product with deionized water for 4-6 times, and then washing it with anhydrous ethanol for 4-6 times, and finally obtaining an Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction CO2 catalyst, i.e. a composite photothermal reduction CO2 catalyst. The invention is obtained through a sol system co-precipitation reaction at room temperature, avoiding the problems of long preparation cycle and complex process of the existing ion exchange method and molten salt method, and the reaction process is relatively simple and does not require complex equipment and harsh reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a method for preparing a composite photothermal reduction CO2 catalyst by a co-precipitation method. Background Art

[0002] With the acceleration of the global industrialization process, the concentration of carbon dioxide in the atmosphere continues to rise, causing a series of serious environmental problems, such as global warming and sea level rise. Therefore, the reduction and resource utilization of carbon dioxide has become one of the key areas of scientific research today. Converting carbon dioxide into valuable chemicals or fuels not only helps to reduce the content of carbon dioxide in the atmosphere and alleviate the greenhouse effect, but also realizes the recycling of carbon resources, which is of great strategic significance. Photothermal reduction of carbon dioxide technology, as an emerging method of carbon dioxide conversion, has unique advantages. It can use solar energy to drive the conversion reaction of carbon dioxide under mild reaction conditions, converting carbon dioxide and water into fuels or other chemicals such as carbon monoxide (CO) and methane (CH4). Compared with the traditional thermal catalytic reduction of carbon dioxide method, the photothermal reduction process can be carried out at a lower temperature, reducing energy consumption; at the same time, the use of solar energy makes it sustainable and environmentally friendly.

[0003] Ag9(SiO4)2NO3 is a new type of broad-spectrum responsive photocatalytic material with potential application value in the field of photocatalysis. However, its existing preparation methods, such as ion exchange method and molten salt method, have many problems. The ion exchange method usually requires cumbersome steps and long reaction time to achieve ion exchange and material synthesis, resulting in a long preparation cycle; the molten salt method has strict requirements on reaction conditions, requires special conditions such as high temperature, and has a complex process and high energy consumption. These problems limit the large-scale preparation and application of Ag9(SiO4)2NO3. In addition, although Ag9(SiO4)2NO3 has certain photocatalytic activity, the performance of CO2 photothermal reduction alone is not ideal and cannot meet the needs of efficient CO2 conversion.

[0004] In the field of photocatalysis, the use of co-catalysts is of great significance for improving the performance of catalysts. Co(OH)2, as a common co-catalyst, has unique physical and chemical properties. It can form a synergistic effect with other photocatalytic materials, promote the separation and transmission of photogenerated carriers, and thus improve the efficiency of photocatalytic reactions. Studies have shown that in some photocatalytic systems, the introduction of Co(OH)2 as a co-catalyst can significantly improve the activity and selectivity of the catalyst. However, in the study of Ag9(SiO4)2NO3 photothermal reduction of CO2, there are relatively few studies on combining Co(OH)2 with Ag9(SiO4)2NO3 and preparing composite catalysts by coprecipitation, and there is no mature preparation process and performance optimization strategy. Therefore, the development of a simple and efficient method for preparing Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst is of great practical significance for improving the performance of CO2 photothermal reduction and promoting the development of photothermal catalytic technology in the field of CO2 resource utilization. The present invention aims to solve the problems of complex Ag9(SiO4)2NO3 preparation process and low CO2 photothermal reduction performance in the prior art, and to provide an environmentally friendly, simple and efficient co-precipitation preparation technology. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a composite photothermal reduction CO2 catalyst by a co-precipitation method.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a composite photothermal reduction CO2 catalyst by a coprecipitation method comprises the following preparation steps:

[0008] S1. Add 2-6g of nano-SiO2 powder and 2-8g of NaOH to 48-60g of the modifier to obtain a silicon source solution;

[0009] S2. 25-33 g of silver nitrate powder was slowly added to the silicon source solution obtained in step S1 under mechanical stirring to obtain a preliminary mixed solution;

[0010] S3. 0.4-1.3 g of cobalt nitrate powder is slowly added to the preliminary mixed solution obtained in step S2 under mechanical stirring until precipitation is complete and then filtered to obtain a coprecipitated product;

[0011] S4. The coprecipitated product obtained in step S3 is washed 4-6 times with deionized water, and then washed 4-6 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst;

[0012] Wherein, the preparation of the modifier comprises the following steps:

[0013] S11. Add 20-30g of polyvinyl pyrrolidone to water, stir until completely dissolved, and then add 40-60g of urea to obtain a mixed solution;

[0014] S12. 10-30 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol, and a hexadecyltrimethylammonium bromide solution was obtained after ultrasonic treatment;

[0015] S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir for 10-15 minutes until the mixture is uniformly mixed, thereby finally obtaining a modifier.

[0016] Preferably, the rotation speed of the mechanical stirring in steps S2 and S3 is 400-500 r / min.

[0017] Preferably, the stirring speed during the preparation of the modifier is 300-450 r / min.

[0018] Preferably, the slow adding in step S2 means adding the silver nitrate powder to the silicon source solution in batches within 10-15 minutes.

[0019] Preferably, the slow adding in step S3 means adding the cobalt nitrate powder to the preliminary mixed solution in batches within 3-6 minutes.

[0020] Preferably, the mass concentration of NaOH in step S1 is 40%.

[0021] Preferably, the frequency of the ultrasonic treatment in step S12 is 30-40 kHz, and the treatment time is 10-15 min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention generates products through a co-precipitation reaction of a sol system at room temperature, thereby avoiding the problems of long preparation cycle and complex process of the existing ion exchange method and molten salt method. The reaction process is relatively easy to operate, does not require complex equipment and harsh reaction conditions, and is conducive to large-scale production and application.

[0024] 2. The present invention increases the specific surface area of ​​the obtained product by adding a modifier, provides more reactive sites, helps the adsorption and diffusion of CO2, and is also beneficial to the absorption and scattering of light, thereby improving the light utilization efficiency.

[0025] 3. The solution system of the present invention can provide a basis for the subsequent construction of Ag9(SiO4)2NO3 homogeneous heterojunction or composite materials, which is conducive to further expanding and optimizing the performance of the catalyst.

[0026] 4. The prepared catalyst has good stability in the environment and can maintain catalytic activity for a long time in practical applications, reducing the performance degradation and cost increase caused by catalyst deactivation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a process flow chart for preparing the composite photothermal reduction CO2 catalyst;

[0028] Figure 2 is a flow chart of the preparation process of the modifier of the present invention;

[0029] Figure 3 This is the X-ray diffraction pattern of the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst obtained in Example 1 of the present invention;

[0030] Figure 4 This is the UV-visible diffuse reflectance spectrum of the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst obtained in Example 1 of the present invention;

[0031] Figure 5 The yields of CO and CH4 after the photothermal reduction of CO2 by the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction CO2 catalyst obtained in Example 1 of the present invention (wherein the large figure on the periphery corresponds to the yield of CO, and the attached small figure corresponds to the yield of CH4). DETAILED DESCRIPTION

[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1-5 , the present invention provides a technical solution:

[0034] Example 1

[0035] A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation:

[0036] S1. Take 48g of modifier and add 2g of nano-SiO2 powder and 2g of NaOH with a mass concentration of 40% to obtain a silicon source solution;

[0037] S2. 25 g of silver nitrate powder was added to the silicon source solution obtained in step S1 in 10 portions at 400 r / min under mechanical stirring to obtain a preliminary mixed solution;

[0038] S3. 0.4 g of cobalt nitrate powder was added to the preliminary mixed solution obtained in step S2 in 3 times under mechanical stirring at 400 r / min within 3 min until the precipitation was complete and the coprecipitated product was obtained by filtration;

[0039] S4. The coprecipitated product obtained in step S3 was washed 4 times with deionized water, and then washed 4 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst;

[0040] In this embodiment, the preparation of the modifier comprises the following steps:

[0041] S11. 20 g of polyvinyl pyrrolidone was added to water and stirred until completely dissolved, and then 40 g of urea was added to obtain a mixed solution;

[0042] S12. 10 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol and ultrasonically treated at a frequency of 30 kHz for 10 min to obtain a hexadecyltrimethylammonium bromide solution;

[0043] S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir at a speed of 300 r / min for 10 min until the mixture is uniformly mixed, and finally obtain a sufficient amount of modifier.

[0044] Example 2

[0045] A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation:

[0046] S1. Take 60g of modifier and add 6g of nano-SiO2 powder and 8g of NaOH with a mass concentration of 40% to obtain a silicon source solution;

[0047] S2. 33 g of silver nitrate powder was added to the silicon source solution obtained in step S1 in 15 portions at 500 r / min under mechanical stirring to obtain a preliminary mixed solution;

[0048] S3. 1.3 g of cobalt nitrate powder was added to the preliminary mixed solution obtained in step S2 in 6 portions under mechanical stirring at 500 r / min within 6 min until the precipitation was complete and the coprecipitated product was obtained by filtration;

[0049] S4. The coprecipitated product obtained in step S3 was washed 6 times with deionized water and then washed 6 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst;

[0050] In this embodiment, the preparation of the modifier comprises the following steps:

[0051] S11. 30 g of polyvinyl pyrrolidone was added to water and stirred until completely dissolved, and then 60 g of urea was added to obtain a mixed solution;

[0052] S12. 30 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol and ultrasonically treated at a frequency of 40 kHz for 15 min to obtain a hexadecyltrimethylammonium bromide solution;

[0053] S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir at a speed of 450 r / min for 15 min until the mixture is uniformly mixed, and finally obtain a sufficient amount of modifier.

[0054] Example 3

[0055] A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation:

[0056] S1. Take 52g of modifier and add 3g of nano-SiO2 powder and 5g of NaOH with a concentration of 40% to obtain a silicon source solution;

[0057] S2. 29 g of silver nitrate powder was added to the silicon source solution obtained in step S1 in 12 portions at 450 r / min under mechanical stirring to obtain a preliminary mixed solution;

[0058] S3. 0.7 g of cobalt nitrate powder was added to the preliminary mixed solution obtained in step S2 in 4 portions under mechanical stirring at 450 r / min within 4 min until the precipitation was complete and the coprecipitated product was obtained by filtration;

[0059] S4. The coprecipitated product obtained in step S3 was washed 5 times with deionized water and then washed 5 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst;

[0060] In this embodiment, the preparation of the modifier comprises the following steps:

[0061] S11. 25 g of polyvinyl pyrrolidone was added to water and stirred until completely dissolved, and then 50 g of urea was added to obtain a mixed solution;

[0062] S12. 20 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol and ultrasonically treated at a frequency of 35 kHz for 12 min to obtain a hexadecyltrimethylammonium bromide solution;

[0063] S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir at a speed of 350 r / min for 12 min until the mixture is uniformly mixed, and finally obtain a sufficient amount of modifier.

[0064] Example 4

[0065] A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation:

[0066] S1. Take 55g of modifier and add 4g of nano-SiO2 powder and 7g of NaOH with a mass concentration of 40% to obtain a silicon source solution;

[0067] S2. 30 g of silver nitrate powder was added to the silicon source solution obtained in step S1 in 14 portions at 450 r / min under mechanical stirring to obtain a preliminary mixed solution;

[0068] S3. 0.9 g of cobalt nitrate powder was added to the preliminary mixed solution obtained in step S2 in 5 times within 5 min under mechanical stirring at 450 r / min until the precipitation was complete and the coprecipitated product was obtained by filtration;

[0069] S4. The coprecipitated product obtained in step S3 was washed 5 times with deionized water and then washed 5 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst;

[0070] In this embodiment, the preparation of the modifier comprises the following steps:

[0071] S11. 27 g of polyvinyl pyrrolidone was added to water and stirred until completely dissolved, and then 55 g of urea was added to obtain a mixed solution;

[0072] S12. 24 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol and ultrasonically treated at a frequency of 35 kHz for 14 min to obtain a hexadecyltrimethylammonium bromide solution;

[0073] S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir at a speed of 400 r / min for 14 min until the mixture is uniformly mixed, and finally obtain a sufficient amount of modifier.

[0074] Performance Test:

[0075] Attached Figure 3This is the X-ray diffraction pattern of the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst obtained in Example 1 of the present invention. Before the photothermal reaction, Ag9(SiO4)2NO3 at 32.35° and 34.14° can be detected, and the diffraction peaks at 38.02° and 44.37° correspond to unreacted Ag and Co. After photothermal reduction, the phase is converted into Ag, Co and Co(OH)2. After the reaction, the characteristic diffraction peak intensities of Ag at 38.18°, 44.35°, 64.50°, 77.44° and 81.59° increase, the characteristic diffraction peak at 38.18° corresponds to the presence of Co(OH)2, and the characteristic diffraction peak of Co that does not participate in the reaction can be detected at 44.35°.

[0076] Attached Figure 4 This is the UV-visible diffuse reflectance spectrum of the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst obtained in Example 1 of the present invention. The absorption band edge of the catalyst sample is 428nm within the visible light response wavelength range.

[0077] The Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst prepared in Example 1 was tested for photothermal reduction of CO2. Specifically, the input amount of the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst was 0.1 g, and the test method was gas chromatography. The yields of CO and CH4 after CO2 reduction are shown in the attached figure. Figure 5 The test results show that the CO yield at 0℃ is 0.059mmol·g cal -1 ·h -1 , CH4 yield 0.009mmol·g cal -1 ·h -1 ; The yield of CO at 100°C was 0.056 mmol·g cal -1 ·h -1 , CH4 yield 0.012mmol·g cal -1 ·h -1 ; The yield of CO at 200°C was 2.820 mmol·g cal -1 ·h -1 , CH4 yield 0.085mmol·g cal -1 ·h -1 ; The yield of CO at 300°C was 13.577 mmol·g cal -1 ·h -1, CH4 yield 0.160mmol·g cal -1 ·h -1 ; The CO yield at 400°C was 32.969 mmol·g cal -1 ·h -1 , CH4 yield 0.381mmol·g cal -1 ·h -1 Due to the low temperature below 100 °C, the CO yield is only 0.059 mmol·g cal -1 ·h -1 , the CH4 yield is only 0.009mmol·g cal -1 ·h -1 , with the increase of temperature, the production of CO and CH4 gradually increased, indicating that the photothermal synergy helps to further improve the photocatalytic reduction performance, but under the same illumination conditions, the Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst is more inclined to produce CO.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation, characterized in that: The method comprises the following preparation steps: S1. Add 2-6g of nano-SiO2 powder and 2-8g of NaOH solution to 48-60g of the modifier to obtain a silicon source solution; S2. 25-33 g of silver nitrate powder was slowly added to the silicon source solution obtained in step S1 under mechanical stirring to obtain a preliminary mixed solution; S3. 0.4-1.3 g of cobalt nitrate powder is slowly added to the preliminary mixed solution obtained in step S2 under mechanical stirring until precipitation is complete and then filtered to obtain a coprecipitated product; S4. The coprecipitated product obtained in step S3 is washed 4-6 times with deionized water, and then washed 4-6 times with anhydrous ethanol to finally obtain Ag9(SiO4)2NO3 / Co(OH)2 photothermal reduction of CO2 catalyst, i.e., composite photothermal reduction of CO2 catalyst; Wherein, the preparation of the modifier comprises the following steps: S11. Add 20-30g of polyvinyl pyrrolidone to water, stir until completely dissolved, and then add 40-60g of urea to obtain a mixed solution; S12. 10-30 g of hexadecyltrimethylammonium bromide was added to anhydrous ethanol, and a hexadecyltrimethylammonium bromide solution was obtained after ultrasonic treatment; S13. Add the mixed solution into the hexadecyltrimethylammonium bromide solution and stir for 10-15 minutes until the mixture is uniformly mixed, thereby finally obtaining a modifier.

2. The method for preparing a composite photothermal reduction CO2 catalyst by a coprecipitation method according to claim 1, characterized in that: The rotation speed of the mechanical stirring in steps S2 and S3 is 400-500 r / min.

3. The method for preparing a composite photothermal reduction CO2 catalyst by a coprecipitation method according to claim 1, characterized in that: The stirring speed during the preparation of the modifier is 300-450r / min.

4. The method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation according to claim 1, characterized in that: The slow addition in step S2 refers to adding the silver nitrate powder to the silicon source solution in batches within 10-15 minutes.

5. The method for preparing a composite photothermal reduction CO2 catalyst by a coprecipitation method according to claim 1, characterized in that: The slow addition in step S3 refers to adding the cobalt nitrate powder to the preliminary mixed solution in batches within 3-6 minutes.

6. The method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation according to claim 1, characterized in that: The mass concentration of the NaOH solution in step S1 is 40%.

7. The method for preparing a composite photothermal reduction CO2 catalyst by coprecipitation according to claim 1, characterized in that: The frequency of the ultrasonic treatment in step S12 is 30-40 kHz, and the treatment time is 10-15 min.

Citation Information

Patent Citations

  • Composite materials for cathode materials in secondary battery, method of manufacturing the same, and lithium secondary battery including the same

    CN106981630A

  • Preparation method of catalyst for preparation of carbon nanotubes

    CN113101981A